2019
DOI: 10.1016/j.devcel.2019.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Skeletal Stem and Progenitor Cells for Bone Regeneration Is Driven by PDGFRβ Signaling

Abstract: Bone repair and regeneration critically depend on the activation and recruitment of osteogenesis-competent skeletal stem and progenitor cells (SSPCs). Yet, the origin and triggering cues for SSPC propagation and migration remain largely elusive. Through bulk and single-cell transcriptome profiling of fetal osterix (Osx)-expressing cells, followed by lineage mapping, cell tracing, and conditional mouse mutagenesis, we here identified PDGF-PDGFRb signaling as critical functional mediator of SSPC expansion, migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 74 publications
6
93
0
Order By: Relevance
“…In Fig. S3, ONFHexos augmented the number of MSCs by increasing proliferation and decreasing apoptosis, which might be the compensation to the ischemic injury 40,41 . These data indicated that exosomes from the necrotic zone aggravated ONFH by influencing osteogenic differentiation and migration of MSCs.…”
Section: Discussionmentioning
confidence: 90%
“…In Fig. S3, ONFHexos augmented the number of MSCs by increasing proliferation and decreasing apoptosis, which might be the compensation to the ischemic injury 40,41 . These data indicated that exosomes from the necrotic zone aggravated ONFH by influencing osteogenic differentiation and migration of MSCs.…”
Section: Discussionmentioning
confidence: 90%
“…(87) Further, PDGFRβ + skeletal stem and progenitor cells (SSPCs) mainly reside in perivascular niches, and PDGF-PDGFRβ signaling induces SSPC proliferation, trafficking, and angiotropism during bone injury. (88) (106) ; Basic-Jukic and colleagues (147) BMP-4 ; Klimiuk and colleagues (142) ; Zimmermann-Geller and colleagues (143) FGF1 (60) ; Dias and colleagues (61) IL-33 Romeo and colleagues (39) Nidogen-1 ; Song and colleagues (38) Tenascin-C Romeo and colleagues (39) TNF-α Carlson and colleagues (182) Vascular roles of fibroblast growth factor Fibroblast growth factors (FGFs) are mainly secreted by bone lineage cells, including chondrocytes and osteoblasts, (89,90) and the receptors FGFR1 and FGFR2 expressed in vascular cells. (91) FGFs induces the expression of multiple angiogenic molecules, including VEGFA and VEGFR2, stimulating the growth of blood vessels and contributing to chondrocyte proliferation and the initiation of chondrocyte hypertrophy.…”
Section: Role Of Vegfa During Bone Developmentmentioning
confidence: 99%
“…Indeed, LepR+ cells express both PDGFRα ( Pdgfra ) and PDGFRβ ( Pdgfrb ) ( Sugiyama et al, 2006 ; Zhou B.O. et al, 2014 ), whose ligands PDGF-B and PDGF-D are produced by endothelial cells (and pre-osteoclasts) ( Xie et al, 2014 ; Böhm et al, 2019 ). The existence of such crosstalk is supported by the recent finding that ablation of PDGFRβ from Osx-Cre-positive cells has no effect on bone formation, but lowers the contribution of Osx-traced cells to fracture healing and impaired vascularization of the callus ( Böhm et al, 2019 ).…”
Section: The Perivascular Niche In Adult Bonementioning
confidence: 99%
“…This aligns well with the previous observation that Osx-Cre mediated ablation of β-catenin causes a shift of the fate of targeted cells to the adipogenic line ( Song et al, 2012 ). However, in this context it should not be forgotten that Osx-Cre targets a number of different types of cells, including osteoprogenitors, pericytes and bm-SSPCs ( Mizoguchi et al, 2014 ; Böhm et al, 2019 ).…”
Section: The Perivascular Niche In Adult Bonementioning
confidence: 99%
See 1 more Smart Citation